2020
DOI: 10.1177/0013916520950270
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Co-location: Visual Connections of Staff Workstations and Staff Communication in Primary Care Clinics

Abstract: The importance of communication among healthcare providers has been long recognized, and many healthcare organizations are implementing team-based care, with emphasis on staff communication. While previous empirical studies in various settings illustrate the role of built environments in user communication, there is a lack of quantified interpersonal spatial metrics to predict interactions. This study investigates how interpersonal spatial metrics at different scales predict staff communication patterns by emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 47 publications
0
18
0
1
Order By: Relevance
“…For instance, more frequent communication was reported in spaces with more integrated overall layout [31][32][33], in workspaces with accessible shared team spaces [18,34,35], and in locations that are more accessible to all other spaces [36]. Furthermore, more frequent face-to-face interactions were reported among individuals in close physical distance, such as those who were on the same floor or corridor [37], co-located in the same space [16,38], and proximate to each other's workstations [19,20]. Additionally, visual connections among individuals, such as visibility between workstations [19,39] or visibility from workstations to overall space [40], were found to be significantly associated with more frequent face-to-face communications.…”
Section: Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, more frequent communication was reported in spaces with more integrated overall layout [31][32][33], in workspaces with accessible shared team spaces [18,34,35], and in locations that are more accessible to all other spaces [36]. Furthermore, more frequent face-to-face interactions were reported among individuals in close physical distance, such as those who were on the same floor or corridor [37], co-located in the same space [16,38], and proximate to each other's workstations [19,20]. Additionally, visual connections among individuals, such as visibility between workstations [19,39] or visibility from workstations to overall space [40], were found to be significantly associated with more frequent face-to-face communications.…”
Section: Communicationmentioning
confidence: 99%
“…The design of workspaces in primary care clinics can facilitate teamwork by creating affordances for these four teamwork aspects (i.e., communication, situational awareness, heads-down work, and perception of teamness), and effectively balancing potentially competing needs such as heads-down work and communication [19,20]. In our previous studies of primary care clinics, we found that the overall co-location of staff predicted improved perception of teamwork [21], proximity among staff workstations facilitated frequent communication [19], and specific design factors such as visibility of exam room doors encouraged situational awareness; teams could easily locate providers and could more easily understand if patients had been seen [20].…”
Section: Case Study: Unpacking the Design And Teamwork Model In Primary Care Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This article is a part of a larger study investigating the role of spatial attributes in teamwork experiences, including staff backstage communication (Lim, Kanfer et al, 2019) and face-to-face communication patterns (Lim et al, 2020), in primary care clinics. As part of the study, this article focuses on the relationships between visual attributes and teamwork perceptions of staff members and patients.…”
Section: Settingsmentioning
confidence: 99%
“…First, as part of the larger study, behavior mapping observations were conducted, recording locations of individuals with their roles, postures, communication counterparts, and associated devices. This study focuses on staff-patient interaction data from the larger data set (refer to Lim et al, 2020, for further information regarding behavior mapping observations). Also, interactions and associated data that were not captured during behavior mapping observations were qualitatively recorded.…”
Section: Outcome Measurementsmentioning
confidence: 99%